The Effect of Profitability, Leverage, and Company Size on Tax Avoidance Agricultural Products Companies - Erlisa, Ayunda; Hati Nurvi Archelly, Dini; Nur Nilamsari, Intan; Safira Adhani, Tazkia; Hasna Kurniawati, Zhafira; Amrulloh, Amri (Journal Economic Business Innovation, 2024)
This study looks into the connections between tax evasion, company size, leverage, and profitability in manufacturing firms that produce goods for the agricultural products sector. Analysis was done on data from 49 food and beverage firms that were listed on the Indonesia Stock Exchange in 2022 using positivist quantitative research approaches. The sample was selected via purposive sampling, and secondary data from annual reports were obtained and analyzed using standard assumption tests and multiple linear regression analysis. The study revealed that tax avoidance behavior is significantly influenced by profitability, leverage, and company size. Higher leverage was found to be correlated with less tax avoidance, in line with prior studies. Nevertheless, the lack of a substantial correlation between profitability and tax avoidance contradicts earlier research, suggesting that environmental factors may play a role. The study's findings emphasize the significance of taking into account industry dynamics, regulatory settings, and firm-specific techniques when comprehending tax avoidance behavior. Additional investigation is required to examine these factors and their consequences for company decision-making and regulatory frameworks. This research adds to the body of knowledge by offering insightful information about the factors that influence tax evasion in manufacturing businesses that produce goods for the agricultural products sector.